Dialysis Pretreatment for Dissolved Organic Nitrogen Analysis in Freshwaters - Qiang Wang; Bin Hua; John Yang; Fengjing Liu; Guocheng Zhu; Baolin Deng (Journal of Chemistry)
Total dissolved nitrogen (TDN), including dissolved inorganic nitrogen (DIN) and dissolved organic nitrogen (DON), plays an important role in numerous environmental processes, such as nutrient cycling and lake and estuary eutrophication. The impact of DIN on environmental processes has been extensively studied. However, the understanding on DON in the environment is largely unknown, as there is no direct method for DON measurement. In practice, DON was determined by subtracting DIN from TDN. Large measurement errors could be induced when DIN becomes dominant in sample. This study was to investigate the impact of two pretreatments of dialysis, dialysis against Millipore water and dialysis against phosphate buffer (4.7 mM H3PO4-5.3 mM KH2PO4, pH 2.2) using a cellulose ester (CE) membrane (100–500 Da molecular weight cutoff), on DON measurement in a broad DIN range from various aquatic ecosystems. Results showed that the removal of NH4-N and NO3-N by both dialysis approaches was highly effective (>80%), but the DON loss by the former was significantly lower than by the latter. This study demonstrated that dialysis against Millipore water with the membrane would be more effective as a sample pretreatment for DIN removal, leading to a reliable and accurate DON measurement.